God and the pandemic : a Christian reflection on the coronavirus and its aftermath - Wright, N. T. (Nicholas Thomas) (Nicholas Thomas) (Grand Rapids, Michigan : : Zondervan, 2020)
Discover a different way of seeing and responding to the Coronavirus pandemic, an approach drawing on Scripture, Christian history, and the way of living, thinking, and praying revealed to us by Jesus. What are we supposed to think about the Coronavirus crisis? Some people think they know: "This is a sign of the End," they say. "It's all predicted in the book of Revelation." Others disagree but are equally clear: "This is a call to repent. God is judging the world and through this disease he's telling us to change." Some join in the chorus of blame and condemnation: "It's the fault of the Chinese, the government, the World Health Organization..." N. T. Wright examines these reactions to the virus and finds them wanting. Instead, he shows that a careful reading of the Bible and Christian history offers simple though profound answers to our many questions, including : What should be the Christian response? How should we think about God? How do we live in the present? Why should we lament? What should we learn about ourselves? How do we recover? Written by one of the world's foremost New Testament scholars, God and the Pandemic will serve as your guide to read the events of today through the light of Jesus' death and resurrection.
Where do we start? -- Reading the Old Testament -- Jesus and the Gospels -- Reading the New Testament -- Where do we go from here?
Keywords: Suffering -- Religious aspects -- Christianity; COVID-19 (Disease) -- Religious aspects -- Christianity; Epidemics -- Religious aspects -- Christianity; Diseases -- Religious aspects -- Christianity; Suffering -- Religious aspects -- Christianity..; COVID-19 (Disease) -- Religious aspects -- Christianity..; Diseases -- Religious aspects -- Christianity..; Epidemics -- Religious aspects -- Christianity..